DEVELOPMENT OF AN INTERACTIVE FLIPBOOK-BASED E-MODULE TO ENHANCE STUDENTS’ ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS IN ARITHMETIC SEQUENCES AND SERIES - Nuranita Adiastuty; Sumarni Sumarni; Nunu Nurhayati; Siska Siti Rukoyah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study addresses the challenges in the learning process, particularly the reliance on textbooks and limited instructional materials, leading to low mathematical conceptual understanding among students, especially in arithmetic sequences and series. To tackle this issue, an interactive flipbook-based e-module was developed to enhance students’ conceptual understanding. The aim of this study is to create valid, practical, and effective teaching materials in the form of this e-module. Using the ADDIE development model, the research comprises five phases: Analysis, Design, Development, Implementation, and Evaluation. Data analysis techniques include tests for validity, practicality, and improvements in conceptual understanding. Validity analysis yielded scores of 92.36% from media experts and 87.84% from content experts, both classified as “very valid.â€ Practicality analysis resulted in a score of 78.33% from teacher responses (categorized as “practicalâ€) and 81.56% from student responses (categorized as “very practicalâ€). The e-module successfully enhances conceptual understanding, with average pretest and posttest scores of 16.91 and 23.04, respectively. N-Gain analysis indicates an average N-Gain score of 0.88, classified as “high.â€ In conclusion, the developed interactive flipbook-based e-module is valid, practical, and effective in improving students' mathematical conceptual understanding.